Interpretacja stanowisk prahistorycznych Niaux i la Vache w Pirenejach jako „miejsc pamięci” i „krajobrazu pamięci” - Głód, Anna (Folia Praehistorica Posnaniensia, 2019)
This article is an attempt to interpret Niaux prehistoric sites (where rites and rock paintings were discovered) and La Vache (the place where the prehistoric people were camped) in the Pyrenees as “sites of memory” and “landscape of memory”. The article attempts to answer the question of whether cave positions that are the subject of the work can be interpreted and defined as “sites of memory” from a modern point of view, and whether the cave in Niaux could be a kind of “site of memory” for the prehistoric population. Additionally, whether the area within which these two caves are located can be considered as part of the “landscape of memory”.